2019
DOI: 10.1371/journal.ppat.1007375
|View full text |Cite
|
Sign up to set email alerts
|

An anti-Gn glycoprotein antibody from a convalescent patient potently inhibits the infection of severe fever with thrombocytopenia syndrome virus

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease localized to China, Japan, and Korea that is characterized by severe hemorrhage and a high fatality rate. Currently, no specific vaccine or treatment has been approved for this disease. To develop a therapeutic agent for SFTS, we isolated antibodies from a phage-displayed antibody library that was constructed from a patient who recovered from SFTS virus (SFTSV) infection. One antibody, designated as Ab10, was reactive to the G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 67 publications
0
43
0
Order By: Relevance
“…In the present study, we describe the natural history of disease and pathogenesis of SFTSV infection in IFNAR -/mice with a focus on profiling the inflammatory cytokine response and resolving the onset of vascular leak to facilitate comparisons between recent reports correlating cytokine levels in human cases of SFTS with disease severity [17][18][19][20][21]. Similar to several recent reports with other strains of SFTSV [22,23], we found that IFNAR -/mice are highly sensitive to the virus with a single PFU challenge dose achieving uniform lethality. Consequently, we selected a 3 PFU SC challenge dose in our natural history study to resemble a low-dose human exposure.…”
Section: Discussionmentioning
confidence: 82%
“…In the present study, we describe the natural history of disease and pathogenesis of SFTSV infection in IFNAR -/mice with a focus on profiling the inflammatory cytokine response and resolving the onset of vascular leak to facilitate comparisons between recent reports correlating cytokine levels in human cases of SFTS with disease severity [17][18][19][20][21]. Similar to several recent reports with other strains of SFTSV [22,23], we found that IFNAR -/mice are highly sensitive to the virus with a single PFU challenge dose achieving uniform lethality. Consequently, we selected a 3 PFU SC challenge dose in our natural history study to resemble a low-dose human exposure.…”
Section: Discussionmentioning
confidence: 82%
“…Two anti-Gn SFTS neutralizing antibodies, Mab4-5 and Ab10, isolated from a phage display library of SFTS patient antibodies, were reported earlier (25,26). Only Ab10 was evaluated for the inhibition of SFTSV infection in an A129 mouse model without monitoring SFTSV titer in vivo during the treatment (26). In the current study, we reported the isolation of Gn-specific single-domain antibodies from an immunized camel and the comprehensive characterization of the neutralizing activity of the nanobody.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, there is an urgent need for therapeutics or vaccines for SFTSV infection in humans and animals. Two anti-Gn SFTS neutralizing antibodies, Mab4-5 and Ab10, isolated from a phage display library of SFTS patient antibodies, were reported earlier (25,26). Only Ab10 was evaluated for the inhibition of SFTSV infection in an A129 mouse model without monitoring SFTSV titer in vivo during the treatment (26).…”
Section: Discussionmentioning
confidence: 99%
“…Following induction with 0.1 mM isopropyl β-D-thiogalactoside (IPTG) for 18 h at 16˚C, the protein was purified using HisTrap HP histidine-tagged protein columns (GE healthcare, Chicago, IL, USA) according to the manufacturer's instruction. Recombinant Gn and Gc glycoproteins fused to Fc region of human immunoglobulin heavy chain were purified as previously described [19]. Briefly, vectors cloned with gene encoding Gn or Gc were transfected into HEK293F cells (Thermo Fisher Scientific, Waltham, MA, USA) using polyethylenimine.…”
Section: Preparation Of Recombinant Proteinsmentioning
confidence: 99%